Clinimetric Properties of Self-reported Disability Scales for Whiplash: A Systematic Review for the Whiplash Core Outcome Set (CATWAD). Issue 10 (October 2021) - Griffin, Alexandra R.; Leaver, Andrew M.; Arora, Mohit; Walton, David M.; Peek, Aimie; Bandong, Aila N.; Sterling, Michele; Rebbeck, Trudy
Abstract : Objectives: A core outcomes set (COS) for whiplash-associated disorders (WADs) has been proposed to improve consistency of outcome reporting in clinical trials. Patient-reported disability was one outcome of interest within this COS. The aim of this review was to identify the most suitable tools for measuring self-reported disability in WAD based on clinimetric performance. Methods: Database searches took place in 2 stages. The first identified outcome measures used to assess self-reported disability in WAD, and the second identified studies assessing the clinimetric properties of these outcome measures in WAD. Data on the study, population and outcome measure characteristics were extracted, along with clinimetric data. Quality and clinimetric performance were assessed in accordance with the Consensus-based Standards for the Selection of Health Status Measurement Instruments (COSMIN). Results: Of 19, 663 records identified in stage 1 searches, 32 were retained following stage 2 searches and screening. Both the Whiplash Disability Questionnaire and Neck Disability Index performed well in reliability (intraclass correlation coefficient=0.84 to 0.98), construct validity (74% to 82% of hypotheses accepted), and responsiveness (majority of correlations in accordance with hypotheses). Both received Category B recommendations due to a lack of evidence for content validity. Discussion: This review identified the Neck Disability Index and Whiplash Disability Questionnaire as the most appropriate patient-reported outcome measures (PROMs) for assessing self-reported disability in WAD based on moderate to high-quality evidence for sufficient reliability, construct validity and responsiveness. However, the content validity of these PROMs has yet to be established in WAD, and until this is undertaken, it is not possible to recommend 1 PROM over the other for inclusion in the WAD COS. Abstract : Supplemental Digital Content is available in the text.